Restrictions on the Judge's Authority to Supervise the Application of the Principles Governing the Contractual Criminal Authority of the Administration in Comparative and Iraqi Law - Hassan, Shorouk; ALmakzomy , Waleed (Journal of Legal Sciences, 2026)
This study aims to shed light on the constraints imposed on a judge’s authority when exercising judicial review of the administration’s adherence to its governing principles, specifically in the context of imposing administrative sanctions on its contractors. The research classifies these constraints into two main types:• Formal Constraints: Arising either from the nature of certain administrative contracts or from the legal basis on which they rest, such as mandatory legislative provisions or explicit contractual clauses contained within the contract’s terms.• Substantive Constraints: Consisting of a set of rules governing the legitimacy of a sanction, including: the prohibition on infringing personal liberty or other fundamental rights without legal authority; the ban on imposing multiple sanctions for the same violation in order to uphold the principle of single sanction; and the consideration of exceptional circumstances—such as emergencies, force majeure, or mutual error by both the administration and the contractor—that may limit the legitimacy of imposing a sanction.The importance of these constraints lies in their role as essential exceptions to both the administration’s discretionary power and the scope of judicial review, requiring a precise understanding of the balance needed between protecting the public interest and safeguarding contractors’ rights.